Natural pyrethrins induce autophagy of HepG2 cells through the activation of AMPK/mTOR pathway. (October 2018) - Yang, Yun; Gao, Jufang; Zhang, Yang; Xu, Wenping; Hao, Youwu; Xu, Zhiping; Tao, Liming
Abstract: Natural pyrethrins, one kind of insects' neural toxin, have been used worldwide for the control of pests of crops, livestock, and human beings. However, their specific mechanisms of action are incompletely understood and hence further investigation is required. Here we used a series of experiments including colony formation, fluorescent staining, western blotting, enzyme activity detection, immunofluorescence analysis, and real-time quantitative PCR (QPCR) to investigate whether natural pyrethrins (0–40 μg/mL) are able to modulate autophagy process through AMPK/mTOR signaling pathway, in order to reveal their cytotoxic mechanisms. The results showed that natural pyrethrins markedly inhibited the proliferation of HepG2 cells in both concentration- and time-dependent manners. Particularly, natural pyrethrins could induce the resulting autophagosome, and the intensification of LC3-II formation and translocation, the accumulation of Beclin-1 and the reduction of p62 and thus autophagy. We clarified that natural pyrethrins induced the abnormal level of oxidation reduction metabolism, leading to mitochondrial permeability transition pore (mPTP) opening, ATP depletion and mitochondria eliminating by autophagy. Moreover, the phosphorylation levels of AMPK were significantly enhanced, and the mTOR and p70s6k phosphorylation were drastically decreased. These results showed that natural pyrethrins induced autophagy of HepG2 cells and activation of the AMPK/mTOR signaling pathway might have potential risk to human health. Graphical abstract: Schematic representation of natural pyrethrins mediated autophagy and showed the inhibition of AMPK/mTOR signaling pathway in HepG2 cells. Highlights: Natural pyrethrins has a potential risk to human health. We detect the antiproliferative effect of natural pyrethrins on HepG2 cells. Natural pyrethrins could induced autophagy in HepG2 cells. Natural pyrethrins induces AMPK/mTOR pathway dependent autophagy. Natural pyrethrins arouse abnormal level of oxidation reduction metabolism.